Effect of Camellia flava (Pitard) Sealy flower extract on the degeneration of Islets of Langerhans and insulin resistance in alloxan-induced hyperglycemia model on Swiss albino mice - Huu Lac Thuy Nguyen; Thi Thu Phuong Ha; Ngoc Phuc Nguyen Nguyen; Nguyen Hoang Linh Phan; Dang Thuy Hien Nguyen; Van Dat Truong; Minh Nhut Truong; Thao-My; Thi Nghia Luu; Ngoc Phuc Nguyen; Thanh Binh Nguyen; Huynh Nhu Mai (Pensoft Publishers, 2024)
Diabetes has always been a matter of concern to health experts as well as the community due to the increasing number of patients with diabetes and the severe consequences it may cause. Many attempts have been made to discover new treatment options for diabetes, and herbal medicines are currently considered to have great potential. This study was conducted to evaluate the effect of Camellia flava flower extract on the degeneration of the islets of Langerhans and insulin resistance in an alloxan-induced hyperglycemia model in Swiss albino mice. Hyperglycemic conditions were induced by alloxan (55 mg/kg, i.v.). The animals were then treated with glibenclamide (10 mg/kg, p.o.) and flower extract at doses of 1.09 and 2.19 g/kg, p.o. The results showed that the blood glucose, AUC, HbA1c, and HOMA-IR levels of two groups of mice receiving flower extract were considerably lower than those of the hyperglycemic untreated group (p < 0.05). The body weights of these two groups were also lower than the untreated group on the last day of the experiment, though the differences were not significant (p > 0.05). However, this was not observed when assessing insulin levels as well as relative organ weights. In biochemical tests, creatinine and AST and ALT concentrations were evaluated. There was no significant variation in creatinine and AST concentrations between the five experimental groups, whereas mice treated with glibenclamide and flower extract at both doses showed a remarkable decline in ALT concentration (p < 0.05). The hepatic histomicrographs were consistent with ALT results, while the H&E staining of kidneys showed no difference between groups. Histomicrographs of the pancreas revealed that the treatment groups using glibenclamide and flower extract had larger islets of Langerhans than those of the alloxan-treated group. Based on these results, this study demonstrated that Camellia flava flower extract exerted several beneficial effects, including blood sugar level reduction, weight loss promotion, and organ protection, hence making it a new potential herbal medication for the management of diabetes.